Growth of vascular smooth muscle cells on collagen I exposed to RBL-2H3 mastocytoma cells - Maxová, Hana; Bacáková, Lucie; Eckhardt, Adam; Miksík, Ivan; Lisá, Vera; Novotná, Jana; Herget, Jan (Cellular physiology and biochemistry, 2010)
Remodeling of the peripheral pulmonary vasculature during chronic hypoxia is characterized by accelerated collagenolysis and thickening of the vascular wall. Low molecular weight peptides, products of cleavage by interstitial collagenase and muscular layer in the peripheral pulmonary vessels, are typically present. The aim of this "in vitro" study was to verify that mast cells (RBL-2H3) as a potent source of a variety of biomolecules which can affect vessel wall remodeling are capable of splitting collagen and then facilitating the growth of vascular smooth muscle cells (VSMC). Collagen I was exposed to RBL-2H3 cells cultured 48 hours under normoxic or hypoxic (3% O(2)) conditions and then seeded with VSMC. The VSMC proliferated with the shortest doubling time and reached the highest cell population density on the collagen pre-modified with hypoxic RBL-2H3 cells. This increased growth activity of VSMC was probably due to the fragmentation of collagen by proteases released from RBL-2H3 cells. Absolute amount of collagen fragments was similar in samples exposed to normoxic and hypoxic RBL-2H3 cells, but the concentration of at least one collagen fragment was significantly higher under hypoxic conditions. Mast cells exposed to hypoxia are more capable to split collagen and facilitate the growth of VSMC.
Keywords: Molecular Sequence Data; kultivované buňky; nádorové buněčné linie; Rats; sekvence aminokyselin; Cell Adhesion; mastocyty; hypoxie buňky; Aorta; mastocytom; Rats, Wistar; mužské pohlaví; aorta; Collagen Type I; Cell Proliferation; Cell Line, Tumor; kolagen typu I; krysa rodu Rattus; svaly hladké cévní; Muscle, Smooth, Vascular; Cells, Cultured; zvířata; Amino Acid Sequence; proliferace buněk; Mast Cells; buněčná adheze; Mastocytoma; potkani Wistar; molekulární sekvence - údaje; Cell Hypoxia; Male; Animals